STRATEGI PENDIDIKAN LINGKUNGAN UNTUK MENINGKATKAN KESADARAN KONSERVASI SATWA LIAR PADA GENERASI MUDA DI DESA LEAHARI, PULAU AMBON - Sahusilawane, John; Badaruddin, Ernywati (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity was conducted in Leahari Village, Ambon Island, to raise awareness of wildlife conservation among the younger generation through environmental education based on local wisdom. The activity methods included outreach, participatory discussions, mangrove planting, and coastal cleanup, involving 50 participants consisting of students, youth, and community leaders. Evaluation was conducted through pre- and post-tests to measure improvements in knowledge, attitudes, and conservative behavior. Results showed an increase in knowledge from 55% to 90%, attitudes from 60% to 88%, and behavior from 58% to 86%. This activity demonstrated that the integration of local values ​​such as sasi laut and pela gandong is effective in strengthening the ecological awareness of the younger generation.